Erosion and Soil Contamination Control Using Coconut Flakes and Plantation of Centella Asiatica and Chrysopogon Zizanioides - Roslan R.; Omar R.C.; Baharuddin I.N.Z.; Zulkarnain M.S.; Hanafiah M.I.M. (Institute of Physics Publishing, 2023)
Biodiversity; Bioremediation; Biotechnology; Contamination; Engineering research; Erosion; Heavy metals; Pollution detection; Soil conservation; Soils; Sustainable development; Centella asiatica; coconut; Different proportions; Green technology; Land degradation; Phytoremediation; Slope instability; Soil contamination; Soil pollution